Analisa Masalah Pengelolaan Sumber Daya Manusia di PT Sunchirin Industries Indonesia: Studi Kasus di Kawasan Industri Karawang Internasional Indusrtial City (KIIC) - Karma Saputra; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
This research was conducted with the aim of identifying and analyzing the challenges faced in Human Resource Management by PT Sunchirin Industres Indonesia in Karawang International Industrial City. The importance of effective HR in enhancing organizational performance cannot be underestimated. However, several challenges related to recruitment, employee development, and performance management are faced by the company. This study uses a case study method with a qualitative approach, which involves interviews with human resource managers and employees, as well as the analysis of company documents. According to the research findings, PT Sunchirin Industres Indonesia is facing employee retention issues, a lack of leadership development, and a mismatch between performance evaluations and the company's needs.